Implementation of Empowerment Cash Waqf at the Muhammadiyah Organization in Medan City - Yenni Samri Juliati Nst; Sri Ramadhani (AGHNIYA : Jurnal Ekonomi Islam, 2021)
This study aims to find out how the implementation of money waqf exists in the Muhammadiyah organization in the city of Medan. And knowing the challenges in implementing money waqf in the Muhammadiyah mass organization in the city of Medan. As well as knowing the opportunities for money waqf at Muhammadiyah organizations in the city of Medan. Data collection is done by the method of documentation, observation and interviews with the management of the Muhammaadiyah city of Medan. This research was analyzed descriptively qualitatively, with data reduction (Data Reduction), the presentation of data was then drawn conclusions. The results of this study concluded that empowerment of money waqf in Muhammadiyah organizations in the city of Medan had been carried out, namely by cooperating with institutions within the organization (Muhamammadiyah General Hospital and Private Snakma Vocational School), and contracts used in managing the waqf money is with mudharabah. The two challenges in empowering money waqf in Muhamamdiyah organizations are the development of money waqf assets in invested institutions, changes in stewardship, times that are not optimal for the waqf waqf, and still low socialization to the community so that the number of facilitators does not increase. The three opportunities for empowering money waqf in the Muhammadiyah organization in the city of Medan are very broad and potential when viewed from the number of Muhammadiyah members or citizens, as well as the obedient attitude of Muhammadiyah citizens to the decisions of the Muhammadiyah leadership.